Glycemic control after 6 days of insulin pump reservoir use in type 1 diabetes: results of double-blind and open-label cross-over trials of insulin lispro and insulin aspart - Tamborlane, William V; Renard, Eric; Wadwa, R Paul; Blevins, Thomas; Jacober, Scott J; Liu, Rong; D'Souza, Deborah N; Rees, Tina M (Canadian journal of diabetes, 2015)
The objective of the current study was to assess mean self-monitored blood glucose (SMBG), on day 6 of 6 days of continuous reservoir wear (6D), with insulin lispro (Lis) or insulin aspart (Asp). Two 24-week, randomized trials were conducted in subjects with type 1 diabetes treated by continuous subcutaneous insulin infusion (CSII) for ≥6 months, with a mean total daily insulin dose capable of supporting 6 days of in-reservoir use. Study 1 had an open-label, six-sequence, three-treatment, three-period, cross-over design. Study 2 had a double-blind, two-sequence, two-treatment, two-period, cross-over design. The primary efficacy measure was the mean of Day 6, seven-point SMBG profiles for insulin lispro 6D (Lis6D) and insulin aspart 6D (Asp6D) treatment periods. Safety measures were also assessed. Lis did not achieve noninferiority (SMBG; margin = 0.6 mmol/L [10.8 mg/dL]) to Asp on Day 6 of reservoir wear in either Study (least-squares mean difference: Study 1 = 0.48 mmol/L [8.64 mg/dL]; 95% confidence interval [CI] [0.20, 0.76], Study 2 = 0.36 mmol/L [6.49 mg/dL]; 95% CI [0.06, 0.66]). Noninferiority was demonstrated for overall daily mean of SMBG values over days 1 to 6 of reservoir use during each treatment period. In the Lis treatment period, subjects reported a lower documented and total hypoglycemia rate per 30 days and a higher rate of non-explained hyperglycemia than in the Asp treatment period. While the mean blood glucose on Day 6 of Lis6D did not meet non-inferiority, the overall daily mean blood glucose was not different, with a decreased rate of hypoglycemia with Lis.